Patient perceptions, motivations and barriers to treatment adherence in hypertension: results of a questionnaire-based survey in five European countries - Burnier, Michel; Azizi, Michel; Magne, Julien; Prejbisz, Aleksander; Cunha, Vitoria; Gupta, Pankaj; Vaclavik, Jan; Versmissen, Jorie; Cornelissen, Véronique; Dorobantu, Maria; Desideri, Giovambattista; Persu, Alexandre; et al. (Blood pressure, 2025)
AIMS: To assess perceptions, motivations and barriers to treatment adherence depending on emotional, lifestyle, medical and non-adherence risk profiles in hypertensive patients. METHODS AND RESULTS: Cross-sectional data were obtained using an online anonymous survey. Four distinct global risk scores (medical, lifestyle, emotional and quality of life (QoL) and non-adherence risk scores) were calculated based on the responses to specific groups of questions. A total of 2615 treated hypertensive patients (≥18 years of age) from 5 European countries completed the questionnaire. Mean (SD) age was 69.6 years (5.8); 54% males. Overall, antihypertensive therapy represented a low burden in patients' daily life (2.9/10 in the Likert scale). Perfect self-reported adherence was claimed by 59.8% of participants. Reporting of non-adherence episodes to physicians was low (13% always/often). Participants with a high non-adherence risk score had a greater number of associated diseases (obesity, sleep disturbances, depression and cardiac complications), a higher treatment-associated burden on daily life, a greater stress level and more antihypertensive pills per day (p < 0.001 for all). No correlation was found between the clinical and lifestyle risk scores and the risk of non-adherence. The emotional score correlated significantly with the non-adherence risk score (p < 0.001). Comparing patients with a low/middle risk to those with a high risk of non-adherence, female gender and age >65 years were associated with a lower odd ratio of non-adherence whereas depression, stress, family hardships, negative information on drugs and poor information were associated with higher odds of non-adherence. CONCLUSIONS: This large survey reveals several underestimated issues regarding patients' perspective in hypertension. It highlights the impact of emotions, exposure to family hardships, and stress on the risk of non-adherence. Non-adherence is underreported by patients; hence it remains mostly unrecognised.
Keywords: Cross-Sectional Studies; Male; kvalita života; hypertenze; antihypertenziva; Quality of Life; stress; adherence k farmakoterapii; Europe; patient perspective; Aged; Motivation; Life Style; mužské pohlaví; senioři; emotion; quality of life; Hypertension; průzkumy a dotazníky; Evropa; Medication Adherence; senioři nad 80 let; životní styl; lidé; motivace; ženské pohlaví; Humans; Antihypertensive Agents; průřezové studie; Aged, 80 and over; medication; Female; Surveys and Questionnaires; Adherence; lidé středního věku; Middle Aged